Oxygen regulation of TET enzymes. (29th January 2021) - Matuleviciute, Rugile; Cunha, Pedro P.; Johnson, Randall S.; Foskolou, Iosifina P.
Abstract : Hypoxia has a significant impact on many physiological and pathological processes. Over the recent years, its role in modulation of epigenetic remodelling has also become clearer. In cancer, low oxygen environments and aberrant epigenomes often go hand in hand, and changes in DNA methylation are now commonly recognised as potential outcome indicators. TET (ten‐eleven translocation) family enzymes are alpha‐ketoglutarate‐, iron‐ and oxygen‐dependent DNA demethylases and are key players in these processes. Although TETs have historically been considered tumour suppressors, recent studies suggest that their functions in cancer might not be straightforward. Recently, inhibition of TETs has been reported to have positive impact in cancer immunotherapy and vaccination studies. This underlines the current interest in developing targeted pharmaceutical inhibitors of these enzymes. Here, we will survey the complexity of TET roles in cancer, and its hypoxic modulation, as well as highlight the potential of these enzymes as therapeutic targets. Abstract : Low oxygen levels (hypoxia) affect multiple physiological and pathological processes, including the epigenetic landscape. Hypoxia and epigenetics are particularly important in shaping tumours and their microenvironments. TET enzymes are DNA demethylases whose activity and/or expression is directly altered by oxygen availability. Depending on the cell and cancer type, alterations on TET activity and expression can either inhibit or promote tumour progression and adaptation. Here, we discuss the complexity of TET roles in hypoxia and cancer and highlight the potential of these enzymes as therapeutic targets.